2020
DOI: 10.3758/s13414-020-02096-x
|View full text |Cite
|
Sign up to set email alerts
|

The Müller-Lyer line-length task interpreted as a conflict paradigm: A chronometric study and a diffusion account

Abstract: We propose to interpret tasks evoking the classical Müller-Lyer illusion as one form of a conflict paradigm involving relevant (line length) and irrelevant (arrow orientation) stimulus attributes. Eight practiced observers compared the lengths of two line-arrow combinations; the length of the lines and the orientation of their arrows was varied unpredictably across trials so as to obtain psychometric and chronometric functions for congruent and incongruent line-arrow combinations. To account for decision speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…This research stems from pioneering works on the Müller-Lyer illusion induced through mental images (Berbaum & Chung, 1981;Ohkuma, 1986;Watters & Scott, 1989). Despite the abundance of recent work on the Müller-Lyer illusion (Costa et al, 2021;Cretenoud et al, 2020;Schwarz & Reike, 2020;Zhang et al, 2020), no studies are found on the induction of the illusion by mental imagery and few are concerned with the influence of the wings length on the magnitude of the illusion. Also, fine arts students are of the utmost interest because they have certain personality and perceptual traits that seem to be related to resistance to the Müller-Lyer illusion (see, Pérez-Fabello et al, 2016, 2018Pérez-Fabello & Campos, 2011a, b, c, 2022Zhang et al, 2017).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This research stems from pioneering works on the Müller-Lyer illusion induced through mental images (Berbaum & Chung, 1981;Ohkuma, 1986;Watters & Scott, 1989). Despite the abundance of recent work on the Müller-Lyer illusion (Costa et al, 2021;Cretenoud et al, 2020;Schwarz & Reike, 2020;Zhang et al, 2020), no studies are found on the induction of the illusion by mental imagery and few are concerned with the influence of the wings length on the magnitude of the illusion. Also, fine arts students are of the utmost interest because they have certain personality and perceptual traits that seem to be related to resistance to the Müller-Lyer illusion (see, Pérez-Fabello et al, 2016, 2018Pérez-Fabello & Campos, 2011a, b, c, 2022Zhang et al, 2017).…”
Section: The Present Studymentioning
confidence: 99%
“…Many aspects of the Müller-Lyer illusion have already been studied. As stimuli definers, researchers have considered geometric and physical parameters (Cretenoud et al, 2020;DeLucia, 1993;Dragoi & Lockhead, 1999;Saccone & Chouinard, 2019;Schwarz & Reike, 2020;Zhang et al, 2020), neurophysiological factors (de Brouwer et al, 2015;Qiu et al, 2008;Tabei et al, 2015;Weidner et al, 2010;Zhang et al, 2013), the magnitude of the illusion as a function of age (Bondarko & Semenov, 2009;Brosvic et al, 2002), the influence of sociocultural backgrounds (McCauley & Henrich, 2006;Phillips, 2019), the influence of the illusion on interpersonal distance (Brunce et al, 2021), the illusion as related to personality traits (Zhang et al, 2017) and clinical disorders (Chouinard et al, 2013;Costa et al, 2021). Furthermore, there is a copious number of recent studies that deal with the experience of the illusion in a wide variety of animals (Costa et al, 2021;Schwarz & Reike, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While some empirical research has shown this to be the case ( 20 , 22 , 37 ), others, more in line with our results, have found both starting point and drift criterion shifts in base rate ( 38 ) and in payoff manipulations ( 20 ). On the other hand, the Müller-Lyer illusion has been associated with drift rate effects ( 39 ) with similar findings for manipulations aimed at affecting perception such as when manipulating the length of a reference line ( 22 ). It is worth noting that these apparent mixed results are not limited to payoff and base rate manipulations.…”
Section: Discussionmentioning
confidence: 62%
“…While some empirical research has shown this to be the case (Leite & Ratcliff, 2011;Simen et al, 2009;White & Poldrack, 2014), others, more in line with our results, have found both starting point and drift criterion shifts in base rate (van Ravenzwaaij et al, 2012) and in payoff manipulations (Leite & Ratcliff, 2011). On the other hand, the Müller-Lyer illusion has been associated with drift rate effects (Schwarz & Reike, 2020) with similar findings for manipulations aimed at affecting perception such as when manipulating the length of a reference line (White & Poldrack, 2014). The mixed results in previous research may be caused by small differences in experimental designs not directly related to the manipulations of interest.…”
Section: Drift Diffusion Modeling Shows Different Parameter Profiles ...mentioning
confidence: 71%